Effects of Two Modalities of Whole-body Electrostimulation Programs and Resistance Circuit Training on Strength and Power - DʼOttavio, Stefano; Briotti, Gianluca; Rosazza, Cristina; Partipilo, Filippo; Silvestri, Adriano; Calabrese, Cosimo; Bernardini, Andrea; Gabrielli, Paolo Roberto; Ruscello, Bruno (International Journal of Sports Medicine, 2019)
The main purpose of this study was to compare the effects on strength and muscle power of a training program based on two different modalities of whole-body electrostimulation (WB-EMS) with respect to a resistance-training program aimed at improving dynamic strength. Twenty-two subjects participated in this study: Thirteen male (age 25.2±2.8 years; height 1.78±0.1 m; body mass 72.8±6.4 kg; body fat 11.6±2.3%) and nine female (age 28.2±3.5 years; height 1.63±0.05 m; body mass 56.8±7.6 kg; body fat 19.1±4.7%). Participants were randomly assigned to three groups that underwent three different 6-week training programs: two modalities of WB-EMS, based on different electrical parameters (experimental), and circuit training with overloads (control). Force-velocity curves were calculated for each participant before and after treatment. All groups improved their level of strength and muscle power (paired sample t-Test, p<0.01; d>1) with a similar magnitude. No significant differences were observed between groups (two-way 2×3 Anova, p>0.05) at the end of the experimentation. This study suggests that WB-EMS might be considered as a valid and faster alternative – or an important complementary procedure – to a traditional overload-based resistance-training program for the development of the DS.
Keywords: testing; exercising; time-saving; 1-RM; force-velocity curve, EMS